Proceso de ASC - OBSERVACION Y ANALISIS ESPECTRAL PARA MONITOREO DE LA ACTIVIDAD SOLAR (2023)
The Sun is a massive and radiant ball of gas composed of approximately 98% helium and hydrogen and six layers, where nuclear reactions of the aforementioned elements occur. These reactions produce a large amount of energy in the form of short electromagnetic wavelengths called gamma rays, which reach the Earth, contributing an energy value of approximately 173,973.9 terawatts [1]. It is thanks to this energy that we develop new technologies for harnessing solar energy and its study, such as the Parker Solar Probe, which allows the study of magnetic fields and their alterations on the solar surface [2]. Using these alterations as an example, solar activity, such as sunspots, solar storms, planetary transits, among others, will be the central topic of study and research carried out by the Quasar Research Group at EAFIT University. The aim is to capture and disseminate valuable information through basic observations using the instruments available in the optics laboratory.